An Ancient Harbour in the District of Alanya - Gülay Tıgrel (Belleten, 1975)

(untitled)
The extensive plain, that borders the south coast of Asia Minor from Antalya to the river Melas, is the ancient Pamphylia. To the east of this, where the Taurus mountains gradually approach the coast, lies the geographically contrasting region of Rough Cilicia. The borders of Pamphylia, especially the eastern extremity which interests us mainly, have always been a matter of different concepts among the ancient authors. We accept the general fact that Side is the last Pamphylian city, and so the east of the river Melas should be regarded as Rough Cilicia. The region, which the present work deals with, is the part of the coast lying between Alara Çay and Kargı Çay in west Cilicia. The accounts of the early explorers, such as Beaufort, Heberdey and Wilhelm, Rott, Keil and Wilhelm, Paribeni and Romanelli, Mitford and Bean, are stili interesting to read but hardly sufficient. Beaufort's attention was attracted by a cape which is located to the east of cape Karaburun and about zo km. to the west of Alanya (Corecesium)